Hydrogen delaying the formation of Guinier-Preston zones in aluminium alloys. (December 2022) - Hachet, Guillaume; Sauvage, Xavier
Graphical abstract: Abstract: The consequences of hydrogen on the formation and growth of GP zones during natural ageing in an Al-5Cu alloy is investigated experimentally down to the atomic scale and numerically using ab initio calculations. As observed through scanning/transmission electron microscopy, the hardening kinetic is delayed due to a slower growth of GP zones during natural ageing when hydrogen is incorporated. According to ab initio calculations, the delayed hardening results from hydrogen trapped in vacancies that reduces significantly the diffusion coefficient of copper and the self diffusion of aluminium. This reduction of the diffusion coefficient is either due to hydrogen being in the path of the atom that exchanges with the vacancy (and increasing the energy barrier) or due to hydrogen being dissociated from the vacancy (and leading to a less stable state).